The Effect of Problem-Based Learning Model on Junior High School Students' Self-Efficacy in Mathematics - Muhammad Zaini; Yerizon Yerizon; Abel Garcia Arlis; Nadya Fitriani (Rangkiang Mathematics Journal, 2025)
Mathematics is an important part of science education and plays an important part in lots of aspects of life. However, students' low self-efficacy in mathematics is often an obstacle in learning. Low self-efficacy can inhibit students' confidence in solving problems and impact on their learning outcomes. One method that might be utilized to improve students' self-efficacy is the Problem-Based Learning (PBL) model. This search aims to analyze the impact of PBL models on their self-efficacy in learning mathematics. This research used quasi-experiment method with Nonequivalent Posttest Only Control Group design. The research sample consisted of fifty-two seventh grade students of SMP IT Madani Islamic School Payakumbuh who were divided into experimental and control groups. The experimental group was treated with PBL model, while the control group used conventional learning. Data was collected through self-efficacy questionnaire and analyzed descriptive and inferential statistical tests. The findings revealed that pupils who studied with PBL models had higher self-efficacy compared to students who used conventional learning models. In conclusion, the application of PBL can increase students' self-efficacy in learning mathematics because this method encourages active involvement, contextual problem solving, and reflection on the thinking process. This research shows the urgency of implementing PBL in mathematics learning to significantly improve students' confidence and learning outcomes.